Analysis of a cell niche with proliferative potential at the roof of the aqueduct of Sylvius. (March 2023) - Martínez-Mendoza, Marianne Lizeth; Rodríguez-Arzate, Cynthia Alejandra; Gómez-González, Gabriela B.; Kirchhoff, Frank; Martínez-Torres, Ataúlfo
Abstract: The aqueduct of Sylvius connects the third with the fourth ventricle and is surrounded by the Periaqueductal Grey. Here, we report a novel niche of cells in the dorsal section of the aqueduct, hereby named dorsal aqueduct niche or DAN, by applying a battery of selective markers and transgenic mouse lines. The somata of DAN cells are located toward the lumen of the ventricle forming multiple layers in close association with the cerebrospinal fluid (CSF). A single process emerges from the soma and run with the blood vessels. Cells of the DAN express radial glia/stem cell markers such as GFAP, vimentin and nestin, and the glutamate transporter GLAST or the oligodendrocyte precursor/pericyte marker NG2, thereby suggesting their potential for the generation of new cells. Morphologically, DAN cells resemble tanycytes of the third ventricle, which transfer biochemical signals from the CSF to the central nervous system and display proliferative capacity. The aqueduct ependymal lining can proliferate as observed by the integration of BrdU and expression of Ki67. Thus, the dorsal section of the aqueduct of Sylvius possesses cells that may act a niche of new glial cells in the adult mouse brain. Highlights: A novel cell niche in the aqueduct of Sylvius. Cells express markers of glial identity and proliferation. Oligodendrocyte precursors are also associated with the dorsal aqueduct niche.